Pemikiran Pendidikan Islam Burhanuddin Az-Zarnuji dan Relevansinya dengan Pendidikan Modern - Firmansyah, Mhd. Yudha; Dewi, Eva; Yumni, Firda Aufa (Journal of Practice Learning and Educational Development, 2026)
This study examines the Islamic educational thought of Burhanuddin Az-Zarnuji and its relevance to modern education systems. Az-Zarnuji was a 12th-century scholar who produced the monumental work Ta'lim al-Muta'allim Tariq at-Ta'allum, which remains a primary reference in Islamic education today. This research employs a qualitative method with a library research approach, analyzing primary and secondary sources related to Az-Zarnuji's thought. The findings indicate that Az-Zarnuji's educational philosophy encompasses fundamental concepts including the essence and virtue of knowledge, the importance of proper intention in learning, teacher-student relationships, gradual learning methodology (tadarruj), and character formation. His learning methods include selecting teachers and study partners, time management, memory reinforcement, and collaborative learning. Az-Zarnuji's thought demonstrates high relevance to modern education, particularly in character education, constructivism learning, learning management, lifelong learning, and holistic education. This study concludes that integrating Az-Zarnuji's thought into contemporary Islamic education systems can provide solutions for producing Muslim generations who excel academically while maintaining noble character.